Pertanggungjawaban Tindak Pidana Pencurian yang Dilakukan oleh Seorang Kleptomania - Komang Sutriani; Ida Ayu Putu Widiati; Ni Made Sukaryati Karma (Warmadewa Press, 2022)
Kleptomania is a condition in which an individual has control problems within himself to take. The mindset here is not only crazy people who are annoyed with reason and mind but also various psychological diseases. There are several cases of frequent thefts caused by kleptomaniac sufferers and in this case a research objectives are formulated, namely regulating the crime of theft committed by a kleptomaniac and criminal liability for the crime of theft committed by a kleptomaniac. This research is a normative legal research with a case and legislation approach. The technique of collecting legal materials that the author uses in this research is a literature study. Sources of legal materials used are primary and secondary legal sources. The legal material analysis technique used is descriptive technique. The findings of this study reveal that cases like this have been regulated in Article 44 paragraph (1) of the Criminal Code. The results from the assessment of the perpetrator at a specialist doctor can be used as legal evidence, to be considered by the judge in determining whether the perpetrator is then placed in a mental health polyclinic or not. in recovery.